Keragaman vektor Plasmodium knowlesi - Paisal Paisal (Balai Litbangkes Tanah Bumbu, 2017)
Plasmodium knowlesi was the fifth Plasmodium which can infect malaria into human. Even though it has already been identified since 1931, the first case of natural human infection was known in 1965. Knowlesi malaria spread among South East Asia where population of monkeys Macaca fascicularis, M. nemestrina, or Presbytis melalophos existed along with malaria vector Anopheles from leucosphyrus group. This review aimed to describe the diversity of P. knowlesi vector. We have done profound literature review on 6 articles from 219 articles related to P. knowlesi published within 2008 to 2015. Our study found that P. knowlesi was recorded only in two countries; Malaysia and Vietnam. In Malaysia, Anopheles cracens, An. introlatus, An. latens, and An. balabacensis were found in Kuala Kapis Pahang, Hulu Selangor, Kapit Serawak, and Kudat Sabah, respectively. While in Vietnam, only a single species An. dirus found to be P. knowlesi vector. This review conclude that positive leucosphyrus mosquitoes most likely to be different among different region. The more abundance, the higher chance of mosquito species to become vector.